Nineteenth Century Spanish American Novels: A Search for Nationness and National Identity - Adhikari, Bam Dev (Literary Studies, 2025)
The article explores the role of literature in the formation of national identity across Spanish America during the nineteenth century. In a time of political upheaval and social change following the wars of independence, novelists sought to define and construct the emerging nationhood of their respective countries. The historical novel, a dominant genre during this period, became a significant medium for reflecting on national origins, celebrating heroic struggles, and articulating the desire for unity and independence. At the same time, the costumbrista novel, rooted in the depiction of everyday life and regional customs, played a crucial role in shaping the cultural aspects of national identity, often through a nostalgic lens that sought to preserve traditional values amid modernization. As Spanish American societies continued to evolve, realist and naturalistic novels emerged, challenging idealized portrayals and instead focusing on the social realities and inequalities that hindered the formation of cohesive national identities. These works highlighted the tensions between the ideal and the real, offering a critical reflection on class struggles, economic challenges, and the tensions between indigenous, African, and European cultural legacies. Through these various novelistic traditions, Spanish American writers navigated the complex and contested terrain of nation-building, revealing the shifting contours of identity in a post-colonial context. This article analyzes these genres and their contributions to the ongoing search for "nationness" in the Spanish-speaking Americas during a formative historical moment.